PENGARUH KETIDAKAMANAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASIONAL (Studi pada Perawat Rumah Sakit PKU Muhammadiyah Yogyakarta) - Ayuri Nurul Kholidah (MNJ 16 UMY 156, 2016)
Objective – The focus of this study is to analyze the influence of job insecurity toward the job performance through organizational commitment. Information obtained from this study is very important to the agency especially to hospital as consideration to minimize the level of job insecurity on the employee. Method – The approach used in this study is quantitative approach. The object of research is PKU Muhammadiyah Yogyakarta hospital with the subject is a nurses. Technique of data collection uses population. Methods of data collection use the census through questionnaires obtained 148 respondents. Data were analyzed by using SEM (Structural Equation Modeling), operated program by AMOS 21,0. The result show that job insecurity has a negative and significant impact on organizational commitment, organizational commitment has a positive and significant impact on job performance, job insecurity has a negative and significant impat on job performance, and last that organizational commitment has a influence and intervening the job insecurity and job performance. Keyword : Job Insecurity, Job Performance, organizational commitment